WHOLE-GENOME SEQUENCING DATA OF KAZAKH INDIVIDUALS - Kairov, Ulykbek; Molkenov, Askhat; Rakhimova, Saule; Kozhamkulov, Ulan; Sharip, Aigul; Karabayev, Daniyar; Daniyarov, Asset; H.Lee, Joseph; D.Terwilliger, Joseph D.; Akilzhanova, Ainur; Zhumadilov, Zhaxybay (BMC Res Notes, 2021)
Kazakhstan is a Central Asian crossroad of European and Asian populations situated along the way of the Great Silk Way. The territory of Kazakhstan has historically been inhabited by nomadic tribes and today is the multi-ethnic country with the dominant Kazakh ethnic group. We sequenced and analyzed the whole-genomes of five ethnic healthy Kazakh individuals with high coverage using next-generation sequencing platform. This whole-genome sequence data of healthy Kazakh individuals can be a valuable reference for biomedical studies investigating disease associations and population-wide genomic studies of ethnically diverse Central Asian region....
Keywords: Whole genome; Kazakh ethnicity; Next-generation sequencing